1985
DOI: 10.1287/mnsc.31.8.970
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Task Size and Similarity on the Decision Behavior of Bank Loan Officers

Abstract: Research on decision-making behavior has shown that decision strategies used by individuals are contingent upon the characteristics of the task. For example, as the task size (i.e., the number of alternatives and/or the number of dimensions describing each alternative) increases, individuals tend to quickly eliminate alternatives that do not meet a criterion level for any dimension (i.e., they adopt a noncompensatory decision strategy, in which a high value on one dimension cannot offset or compensate for a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 33 publications
1
68
1
Order By: Relevance
“…Biggs et al (1985) showed that bank loan officers acquired more information and in a more systematic fashion for loan applicants who were very similar to one another on attributes of interest (e.g., similar values on financial statement strength), relative to dissimilar applicants (differences were large). Similarly, Böckenholt et al (1991) observed that decision makers choosing between vacation locations and restaurants searched for more information when the options differed little rather than a lot on attributes of interest (e.g., in temperature, number of rainy days).…”
Section: Effects Of Assortment Density On Difficulty Of Choicementioning
confidence: 99%
“…Biggs et al (1985) showed that bank loan officers acquired more information and in a more systematic fashion for loan applicants who were very similar to one another on attributes of interest (e.g., similar values on financial statement strength), relative to dissimilar applicants (differences were large). Similarly, Böckenholt et al (1991) observed that decision makers choosing between vacation locations and restaurants searched for more information when the options differed little rather than a lot on attributes of interest (e.g., in temperature, number of rainy days).…”
Section: Effects Of Assortment Density On Difficulty Of Choicementioning
confidence: 99%
“…On the other hand, when a decision task is comparatively simple, decision makers tend to use more complex and effortful decision heuristics such as compensatory decision strategies in which a low value on one attribute can be compensated for by a high value on another attribute. These findings were obtained in studies manipulating time pressure (e.g., Payne et al, 1988;Svenson & Maule, 1993;Wright, 1974;Zakay, 1985), and in studies manipu-lating the numbers of alternatives or attributes (e.g., Biggs et al, 1985;Billing & Marcus, 1983;Kerstholt, 1992;Lohse & Johnson, 1996;Olshavsky, 1979;Payne, 1976;Sundstrom, 1987;Takemura, 1993).…”
Section: Introductionmentioning
confidence: 86%
“…How can we use these metrics to identify decision strategies? We suggest using the metrics in a serial way (for parallel algorithms, see Biggs, Bedard, Gaber, & Linsmeier, 1985;Jarvenpaa, 1989;Todd & Benbasat, 1987). That is, we apply a top-down approach that uses one metric after the other to identify decision strategies.…”
Section: Classification Methodsmentioning
confidence: 99%